THE INFLUENCE OF PRODUCT QUALITY AND PRICE ON PURCHASING DECISIONS AT CIPULIR MARKET, SOUTH JAKARTA - Filma Festivalia; Haryo Wicaksono; Alda Chairani (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
research aims to determine the influence of product quality and price on purchasing decisions at Cipadu Market. to sell in order to be orderly and orderly. This research is a qualitative quantitative research using multiple regression analysis methods. The population in this study were visitors who came to Cipulir Market. Meanwhile, the sample in this study consisted of 100 respondents. The sampling technique is Accidental Sampling